Characterization of Molecular Heterogeneity Associated With Tumor Microenvironment in Clear Cell Renal Cell Carcinoma to Aid Immunotherapy - Zhong, Weimin; Li, Yinan; Yuan, Yichu; Zhong, Hongbin; Huang, Chaoqun; Huang, Jiwei; Lin, Yao; Huang, Jiyi (Frontiers in Cell and Developmental Biology, 2021)
The clear cell renal cell carcinoma (ccRCC) is the most common type of kidney cancer and have a strong immunogenicity. A systematically investigation of the tumor microenvironment in ccRCC could contribute to help clinicians developing personalized treatment and facilitating clinical decision-making. In this study, we analyzed the immune-related subtype of ccRCC on the basis of immune-related gene expression data in the Cancer Genome Atlas (TCGA, N =512) and the International Cancer Genome Consortium (ICGC, N = 90) dataset, respectively. As a result, two subtypes (C1 and C2) were identified by performing non-negative matrix factorization (NMF) clustering. Subtype C1 was characterized by increased advance ccRCC case and immune-related pathways. The higher immune score, stromal score, TMB value, Tumor Immune Dysfunction and Exclusion (TIDE) prediction score and immune checkpoint genes expression level were observed in the C1. In addition, an increasing activated B cell, CD4 T cell and CD8 T cell level were significantly enriched in C1. Also, the C1 subtype might benefit from chemotherapy and immunotherapy. The Patients in subtype C2 have more metabolism-related pathways, higher tumor purity, and a better prognosis. In addition, we also identified some small molecular compounds for the treatment of ccRCC using Connectivity Map (CMap) database. Finally, we constructed and validated an immune-related (IR) score to evaluate immune modification individually. The high IR score was corresponding to a favorable prognosis compared to the low IR score. Moreover, the decreasing IRS score was characterized by more advance tumor stage and grade cases. Another immunotherapy cohort demonstrated patients in higher IR scores group have a significant therapeutic advantages and clinical benefits than the low IR score group. Together, characterization of molecular heterogeneitymay and immune signature will developing new insights into the tumor microenvironment (TME) of ccRCC and provide new strategies for personalized treatment.